The Impact of Salinity in the Irrigation of a Wild Underutilized Leafy Vegetable, Sonchus oleraceus L. - Anna Gkotzamani; Ioannis Ipsilantis; George Menexes; Andreas Katsiotis; Konstadinos Mattas; Athanasios Koukounaras (Plants, 2024)
Introducing non- or under-utilized crops to cultivation generates benefits such as biodiversity enrichment, supporting mitigation actions towards climate change-induced effects. The salinization of soil and water supplies is progressively disrupting natural habitats and food production, especially in regions such as the Mediterranean. Sonchus oleraceus L. is a Mediterranean wild leafy green with nutritional and medicinal properties. This study’s purpose was to determine whether salinity affects the growth, quality, and nutrient composition of Sonchus oleraceus L. In an unheated plastic greenhouse, seedlings were transplanted in pots filled with perlite and irrigated with a nutrient solution with no NaCl added (the control, C) or with the addition of 40, 60, 80, and 100 mM of NaCl (treatments S4, S6, S8, and S10, respectively). The leaf and root growth, leaf quality, and the nutrient composition of leaves and roots were determined. Regarding the results, growth was mainly affected at high salinity levels (S8 and S10), with no observed effects of salinity on the determined quality parameters. The nutrient composition was variably affected by salinity in leaves but not in roots (except in the case of Na and the K/Na ratio). Sonchus oleraceus L. showed a general relative tolerance in moderate salinity levels (40 and 60 mM of NaCl), suggesting potential commercial exploitation of the species in areas where the quality of irrigation water is low. However, the health effects of consuming this species grown under salinity stress need to be studied in future research.